Preoperative Predicting Factors for The Results of Lumbar Spinal Stenosis Surgery (Texas Journal of Medical Science, 2022)
Clinical syndrome is caused by various causes, mainly the muscles of the brigades or the pain of the lower limbs, with or without lower back pain. This study aimed to find out and evaluate Preoperative Predictive Factors for The Results of Lumbar Spinal Stenosis Surgery A cross-sectional study was conducted on patients from Mosul teaching hospital and Tikrit teaching hospital for the period January 2017 to December 2020 who underwent lumbar spinal stenosis without spondylolysthesis. In this study, 100 patients were collected, with ages ranging from 40 years to 800 years, and the patients were distributed according to gender (46 males and 54 women). This study included 100 patients of them, 56 were female (56 %) while the other 44 were male (44%). The body mass index was calculated for all patients and was less than 25 in 20 patients, between 25-30 in 40 patients, and more than 35 in the other 44 patients. The other comorbidities observed were diabetes mellitus in 35 patients, ischemic heart disease in 20 patients, Hypertension in 40 patients and, depression in 40 patients, Smoking observed on eight patients. Lumbar level involvement was L4-L5 in 38 patients, 18 patients in L3-L4, L4-L5, 17 patients in L4-L5, L5- S1 ,12 patients was in L3-L4,L4-L5,L5-S1, 6 patients in L5-S1 ,3 patients in L2-L3 , 4 patients in L2- L3,L3-L4,L4-L5,L5-S1 the study concluded that smoking, cancer or neurological complications, and longer duration of lower extremity pain were all negatively associated with patient satisfaction and good outcome; While the ability to walk better before surgery was positively related to satisfaction at the 6-month follow-up